An ambiguous response to the false dilemmas of philosophical making – the actuality of the Sartrean perspective of Being and Nothingness - de Souza, Thana Mara (Argumentos - Revista de Filosofia, 2025)
The aim of this article is to think about a current issue, the discourse of the Brazilian philosophical making, not worked in the content of Being and Nothingness. However, we think it is possible to bring up some of the themes discussed there, as well as Sartre's philosophical writing, to warn us about the pitfalls of this discourse, which is positioned as the opposite and better than the previous one, but which ends up reproducing what he criticizes by remaining in an excluding dualism. Returning to the Sartrean perspective of thinking in terms of ambiguities, avoiding falling into both realism and idealism, balancing presence to oneself with presence to the world, seems us fundamental, even today, for a more complex discussion, which does not fall into false dilemmas.